Reducing Blood Pressure in Hypertension Patients Using Exercise Intervention Slow Respiratory - Andri, Juli; Padila, Padila; Sugiharno, Ramadhan Trybahari; Andrianto, Muhammad Bagus; J, Harsismanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of slow deep breathing exercises on reducing blood pressure in hypertensive patients in the Telaga Dewa Health Center work area, Bengkulu City. The research method used in this research is quantitative research with a quasi-experimental research design. The results of univariate analysis obtained that the average respondent was 64 years old, with the majority gender being female, namely seven respondents (53.3%). Most respondents have a family history of hypertension, as many as 12 (80%). The results of the bivariate analysis showed that the p-value <0.05. In conclusion, there is a decrease in systolic and diastolic blood pressure before and after slow deep breathing intervention in hypertension sufferers in the Telaga Dewa Health Center Work Area, Bengkulu City. Keywords: Hypertension, Slow Deep Breathing Exercise, Blood Pressure